Numerical investigation of the performances of axial separation helical baffle heat exchangers. (15th October 2016) - Tang, Hongling; Chen, Yaping; Wu, Jiafeng; Yang, Shifan
Highlights: Seriation incline angles of axial separation reduce helical baffle manufacture cost. Adjacent helical baffles are separated by sleeve tubes to form a greater pitch helix. Flow and thermal performances of normal and axial separation schemes were simulated. Deviation of h.t.c. or pressure drop of 21(15)° and 21° schemes is −1.21% or 4.96%. Seriation step of baffle incline angles can be extended to 8° by axial separation. Abstract: Axial separation is a novel baffle connection configuration of circumferential overlap helical baffle heat exchangers which makes baffle incline angle seriation possible. The adjacent baffle plates are separated by sleeve tubes to form a greater pitched helix for enhancing heat transfer under required pressure drop with the least number of molds for reducing baffle manufacture cost. Numerical simulations of flow and heat transfer performances were conducted and the calculation results were verified by the experimental ones. Performance investigation was conducted on eight normal trisection helical baffle schemes with baffle incline angles from 15° to 23° and five axial separation schemes of equivalent 17–22° angles using 15° baffles. In the calculation scope the average deviations of heat transfer coefficients and pressure drops of the normal helical schemes are respectively about −1.97% and −8.11% per 1° deviation of incline angle. The axial separation schemes using 15° baffles with equivalent 21° and 22° incline angles have deviation values of heat transfer coefficient 1.21% and 1.33% lower and pressure drop 4.96% and 5.55% higher respectively than those of the normal 21° and 22° incline angle schemes. By adopting axial separation approach the seriation step of baffle incline angles can be extended to 8°.